(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
In 1976, the most important outbreak of rabies occurred in Argentina. The government adopted different strategies to find an answer to this sanitary problem. The main important was a vaccination campaign using first generation vaccines Fuenzalida- Palacios type (FP), that have been produced in rat sucking brain. At national level, this production has been done in the INPBANLIS “Dr. Carlos G. Malbrán” and resulted in an effective control of the outbreak. Until 2009, 100000 human doses (only for national use) and 50000 veterinary doses (only for outbreak control) have been produced per year. Since 2009, and following OPS-OMS´ recommendations, the government is leading for a replacement of FP vaccines for imported second generation ones for human use and stressed vaccination animal campaigns using similar vaccines produced by private vaccine manufactures. Although endemic areas stay in the north of the country, modifications in bats´ migration patterns have to be consider, due to climate changes. This scene entails an urgent need of veterinary vaccines to make a real sanitary impact. Looking after this challenge, we have been developing cell-culture platforms to approach more technological vaccines. The development of veterinary vaccines using BHK cells as substrate has been done on microcarriers cell culture. We have worked with cell densities between 5 and 8 x 106 cells/ml generating, at least, four harvests with titles of 106 LD50/ml or higher. Three consistent vaccine batches have been produced with a potency of 1 IU/dose or higher. For new national vaccines, we have developed a recombinant canarypox virus in collaboration with the INTA. This virus has the glycoprotein rabies gene among its DNA, extracted of CVS-Malbrán rabies strain, developed in our laboratory. The virus is grown over primary culture of chicken embryo fibroblasts. In non avian hosts, these viruses produce a suicidal infection: they can’t complete its infection cycle, but there’s expression of viral proteins that are processed by host cells, generating a humoral and cellular immune response. This potential vaccine has shown impressive antigenic values, higher than 3.5 IU/ml and the measurement of neutralizing antibodies doesn’t decrease significantly after a year. An advantage of these viruses is the resistance to liofilization process using lactose 10 mg/ml without losing its immunogenicity. In this way, we have realized potency assays that show similar values in comparison with not liofilizated viruses. By these days, we are working hard in developing another recombinant canarypox virus containing only the rabies nucleoprotein gene. The final objective would be a canarypox antirabies vaccine containing both the rabies nucleoprotein and glycoprotein genes.